2009
DOI: 10.1108/09596110910967827
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of capital structure: evidence from Turkish lodging companies

Abstract: PurposeThe purpose of this paper is to investigate the factors affecting capital structure decisions of Istanbul Stock Exchange (ISE) lodging companies.Design/methodology/approachA model based on the trade‐off and pecking order theories is specified and implications of both theories are empirically tested. The model is estimated using a dynamic panel data approach for five ISE companies for the period of 1994‐2006.FindingsThe findings suggest that effective tax rates, tangibility of assets, and return on asset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
121
3
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(157 citation statements)
references
References 60 publications
16
121
3
17
Order By: Relevance
“…The aim is to optimize the firm value and minimalize the capital cost of firm. Study done by Karadeniz et al [20] show that here is a statistically significant relationship between firm size and capital structure. Furthermore, A high firm value shows the welfare of the firm owner.…”
Section: The Indirect Effect Of Firm Size On Firm Value With Capital mentioning
confidence: 99%
“…The aim is to optimize the firm value and minimalize the capital cost of firm. Study done by Karadeniz et al [20] show that here is a statistically significant relationship between firm size and capital structure. Furthermore, A high firm value shows the welfare of the firm owner.…”
Section: The Indirect Effect Of Firm Size On Firm Value With Capital mentioning
confidence: 99%
“…Myers and Majluf (1984) and Myers (1984) assumed an issue of asymmetric information among the managers; who are inside the organization and the investors; who are outside the organization and they developed the Pecking Order Theory. Karadeniz et al (2009) reported negative relationships between leverage and several other variables such as tangibility of assets, effective tax rates and return on assets of Turkish lodging firms; while the tendency of growth, non-debt tax shields, free cash flows and firm size were not proven to be relevant to leverage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other researches have demonstrated the existence of negative impact of capital structure on firm performance such as Ebaid (2009) in listed Egyptian firms, Chakraborty (2010) in India, Karadeniz et al (2009) in Turkish lodging companies and Huang and Sang (2006) in China. Krishnan and Moyer (1997) found a negative and significant impact of total debt to total equity (TD/TE) on Return on Equity (ROE).…”
Section: The Pecking Order Theorymentioning
confidence: 99%